Impactos da adoção de um modelo para gestão da cadeia de suprimentos : um estudo de caso em uma empresa de alimentos - Alves, Pedro Henrique Bortolotto Fagundes (Universidade do Vale do Rio do Sinos, 2008)
The Supply Chain Management has attracted more and more researchers and business men as its benefits have been showed in a variety of company´s sizes. The purpose of this assignment is to present the Supply Chain Management in a food company, particulary in a poutry and dairy chain. It was verify in the literature a privation of SCM models and specially for this two chains (poutry and dairy chain). The author´s intension is to state that the SCM might bring significant positive results under the economic and financial position. The research method used in this assignment is called Design Research. The reason of using this research method is that according to the objective of the issue approached it is necessary to look for the construction of knowledge under a theoretical and practical perspective. To based the research, it was studied the Supply Chain of the poultry and dairy industry. In addition to verify the impacts of the SCM model offered, it was developed one case study for the both chain mentioned bef
Keywords: cadeia suprimentos de frangos e lácteos; design research; estudo de caso; gestão da cadeia de suprimentos; case study; design research; supply chain of poutry and dairy; supply chain management; Engenharias